CO2–brine displacement in heterogeneous carbonates. (February 2015) - Ott, H.; Pentland, C.H.; Oedai, S.
Abstract : Highlights: Multi-phase flow in heterogeneous and dual-porosity carbonate rock. Role of macro and micro-porosity for CO2 -plume migration in aquifers. Larger-scale heterogeneity results in lower fluid-phase mobilities. State-of-the-art numerical history matching of coreflood experiments. Similarities and differences to CO2 -brine displacement in simple sandstone. Abstract: The displacement of brine by CO2 is an important process controlling plume migration and initial pore-space utilization in geological CO2 storage. We present CO2 –brine unsteady-state core flood experiments to characterize CO2 –brine primary displacement in Estaillades limestone, a model system for dual-porosity carbonates. We analyze the experiments by means of numerical simulations assuming 2-D homogeneous rock and parameterized k r ( S W ) relationships. Assisted history matching methodologies were used to find the k r ( S W ) parameters which minimize a mismatch function, giving the best match to the experimental data. We refer the results to the microscopic rock structure and we discuss the limits of applicability. Larger-scale heterogeneity was considered as intrinsic to arrive at a practical and upscaled description of the displacement process. Heterogeneity is discussed by comparing the results to classical relative permeability measurements on samples with a 24× smaller volume, which are less affected by heterogeneity. We found that larger-scale heterogeneity results in lower fluid-phase mobilities.